2018
DOI: 10.1007/s10201-018-0560-4
|View full text |Cite
|
Sign up to set email alerts
|

Different lineages of freshwater jellyfishes (Cnidaria, Olindiidae, Craspedacusta) invading Europe: another piece of the puzzle from Sicily, Italy

Abstract: Correctly identifying and mapping the distribution patterns of passively dispersing freshwater organisms is an important task to understand the mechanisms through which these organisms move across the world and to timely counteract the introduction of invasive alien species; moreover, in the light of the growing evidences of the pervasiveness of cryptic species and cryptic biological invasions among all animal groups, the use of molecular identification tools is strongly advisable.In this context, we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…The considerable increase in freshwater jellyfish sightings between 2011 and 2020 on the one hand may be indicative of an increase in the distributional range and frequency of blooms, but on the other hand, may be a result of increased observational effort in recent years (Minchin et al 2016), also facilitated by the outreach efforts of this study. An increase in distribution and blooming frequency detected by citizen observations could indeed be explained by increasingly favourable conditions for polyp budding of medusae and growth due to climate warming and accelerated transport of stress-resistant podocysts among lakes (Schifani et al 2019). However, at present, there are no quantitative data available supporting one or the other explanation.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…The considerable increase in freshwater jellyfish sightings between 2011 and 2020 on the one hand may be indicative of an increase in the distributional range and frequency of blooms, but on the other hand, may be a result of increased observational effort in recent years (Minchin et al 2016), also facilitated by the outreach efforts of this study. An increase in distribution and blooming frequency detected by citizen observations could indeed be explained by increasingly favourable conditions for polyp budding of medusae and growth due to climate warming and accelerated transport of stress-resistant podocysts among lakes (Schifani et al 2019). However, at present, there are no quantitative data available supporting one or the other explanation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Apart from China, the first main lineage (because not all specimens are the identical haplotypes) is widespread, being detected in Canada/BC, Eastern USA, Uruguay, Chile, and South Italy (Sicily), taking into consideration the lack of some markers, while the second main lineage has been detected (for the moment) in North Africa and central Europe. Schifani et al (2019) used the binomen C. sowerbii for the widely distributed (China, old and new worlds) first main lineage listed here, and C. kiatingi for that present in China and central Europe. However, the morphological variability described for C. sowerbii and the close species (or varieties) C. kiatingi and C. kawaii overlaps (e.g.…”
Section: Morphological and Phylogenetic Remarks On Bc's Craspedacustamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Schifani et al (2018) and Fuentes et al (2019) obtained sequences from specimens identified as C. sowerbii from Sicily (Italy) and Chile, respectively. In their Cox1 analyses, Schifani et al (2018) identified a Sicilian-Grecian-Chinese clade as C. sowerbii, a second German-Chinese clade as C. kiatingi, and a third clade of unknown origin as Craspedacusta sp. (actually, this last sequence was deposited by Dr. P. Schuchert from a polyp stage specimen collected in Ringwiler Weier (Canton Zurich, Switzerland) (see also features part of this sequence in GenBank Accession number MF000493).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…C. sowerbii was first described from specimens found in a water-lily tank in Regent's Park, London, England in 1880 (Lankester, 1880a). Later, the species was reported from many different localities: United States (Garman, 1916), Hawaii, South Australia (Thomas, 1950), New Zealand, the Philippines, China, Japan (Acker, 1976), France, Sweden, Portugal (Ferreira, 1985), Canada (McAlpine et al, 2002), Spain (Pérez-Bote et al, 2006;Medina-Gavilán and González-Duarte, 2018), Mexico (Moreno-Leon and Ortega-Rubio, 2009), Brazil (Silva and Roche, 2007), Uruguay (Mañé-Garzón and Carbonell, 1971), India (Riyas and Kumar, 2017), Italy (Schifani et al, 2018), Chile (Fraire-Pacheco et al, 2017;Fuentes et al, 2019), Turkey (Balik et al, 2001;Bekleyen et al, 2011), Israel (Gasith et al, 2011) and Greece (Karaouzas et al, 2015). From the African continent, it has been recorded with certainty only from South Africa (Rayner, 1988;Rayner andAppleton, 1989, 1992).…”
Section: Introductionmentioning
confidence: 99%